2022
DOI: 10.1017/s1368980022002282
|View full text |Cite
|
Sign up to set email alerts
|

Content of lunchboxes of Dutch primary school children and their perceptions of alternative healthy school lunch concepts

Abstract: Objective: To investigate the content of lunchboxes of primary school children and to examine children’s support and preferences for alternative healthy school lunch concepts. Design: A cross-sectional study among Dutch children from seven primary schools. The content of the lunchboxes was assessed by photographs. Support and preferences for alternative lunch concepts were examined via a self-reported questionnaire. Linear regression analyses were used to investigate the associations bet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 27 publications
0
1
0
Order By: Relevance
“…A cross-sectional study among Dutch children from seven primary schools developed by Rongen et al (2022) evaluated lunchboxes content and the results showed that almost half of children (42,9%) brought sweetened drinks wheareas only 5% of the lunchboxes contained fruits and 6% contained vegetables.…”
Section: Discussionmentioning
confidence: 99%
“…A cross-sectional study among Dutch children from seven primary schools developed by Rongen et al (2022) evaluated lunchboxes content and the results showed that almost half of children (42,9%) brought sweetened drinks wheareas only 5% of the lunchboxes contained fruits and 6% contained vegetables.…”
Section: Discussionmentioning
confidence: 99%